Challenges of Spectators Attendance In Sports Events in Oman - Al-Mufadhali, Salim Said (Πανεπιστήμιο Πελοποννήσου, 2013)
The primary purpose of this study is to develop a clear picture of the challenges to spectator attendance in Oman based on 2009 to 2012 data from the Ministry of Sports Affairs and data from the questionnaires from 411 respondents that the researcher interviewed. Data from the Ministry of Sport Affairs were broken down per year, and per sports complex (Sultan Qaboos Sports Complex, Seeb Sports Complex, Sohar Sports Complex, Nizwa Sports Complex, Sur Sports Complex, Salalah Sports Complex, Al Sa’ada Sports Complex, Ibri Sports Complex, and the Khasab Sports Complex) in order to establish that assumptions that there is a misdistribution of spectators in different sports categories, that sports complexes, especially stadiums, are underutilized, and that even in football, the average attendance per game is still not close to the actual capacity of stadiums. For the questionnaires, six (6) categories were presented: demographic, facilities, time and climate, sports culture, quality of teams, and media/marketing. The overall results show that the reason why spectator attendance is few is because Omani sports culture itself is weak as evidenced by the lack of women among spectators, poor facilities, inability of facilities to counter side effects of climate, weak quality of teams/games, and lack of sports marketing/sponsorship.
Keywords: Spectators; Sports and state - Oman; Sports - Marketing; Sports sponsorship; Sports facilities - Oman; Mass media and sports - Oman; Θεατές; Αθλητισμός και κράτος - Ομάν; Αθλητισμός - Μάρκετινγκ; Αθλητική χορηγία; Αθλητικές εγκαταστάσεις - Ομάν; Μέσα μαζικής ενημέρωσης και αθλητισμός - Ομάν